Orphism in the Poetry of Blaise Cendrars - Howard Nitzberg (Studies in 20th & 21st Century Literature, 1979)
The story of Orpheus has undergone numerous changes in religion and poetry throughout the ages. My essay on Blaise Cendrars is the first study of him in an orphie context. He does not transpose the Orpheus myth directly. Rather, Cendrars contributes to the story of modern orphie poetry by the personal expression he gives to certain orphie concepts and themes. His poetic vision consists of the exploration of his being, the primacy of subjectivity, and the autonomy of the thought processes. Although Cendrars is usually considered an avant-garde poet of the early twentieth century, this article demonstrates that he can be placed in the heritage of Symbolism by the particular use he makes of autonomous thought as a creative means. In this regard, references are made to poems of Mallarmé.
Keywords: Blaise Cendrars; poetry; Orpheus; orphism; symbolism; Mallarmé